Metodologi Politik Negara Kesatuan Republik Indonesia dan Implikasinya terhadap Nalar Nasionalisme Berbasis Keagamaan - Solikhudin, Muhammad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This article attempts to explain the political methodology of the Unitary State of the Republic of Indonesia and its implications for religious-based nationalism. As is known, the Unitary State of the Republic of Indonesia was built with great struggle. Indonesia was born based on a sincere and sincere intention to build an independent unitary state. At the same time to achieve a just, prosperous and prosperous society. A number of events have been passed by this nation. The task of the Indonesian people at this time is to take care of the common house (Indonesia) as a realization of devotion and love for the homeland. Taking care of the Unitary State of the Republic of Indonesia today is by understanding the political methodology of the Unitary State of the Republic of Indonesia, if observed in the contemporary era in Indonesian localities, many political issues with religious nuances are developed. National political issues are strongly influenced by the controversy surrounding SARA (ethnicity, religion, race, and intergroup) wrapped in religious normative arguments. Religion, which should be the teaching and norms of living personality that enlightens every individual, is tainted by the issue of poor quality political interests. Therefore, it is necessary to understand the political methodology of the Republic of Indonesia which includes several aspects such as the harmonization of religion and state. Furthermore, aspects of the concept of democracy in Indonesia are in line with Islamic teachings and the last aspect of national politics is egalitarian and non-violent based which is also in line with religious teachings. All of these aspects will in turn give birth to the reasoning of religious-based nationalism as an ideal and logical implication in seeing the existence of Indonesia which is multicultural and diverse.